Exploring the role of oxytocin in communication processes: A test of the post sex disclosures model. Issue 2 (3rd April 2022) - Denes, Amanda; Crowley, John P.; Dhillon, Anuraj; Bennett-Brown, Margaret; Stebbins, John L.; Granger, Steve W.
ABSTRACT: This study explored the role of the hormone oxytocin in 49 emerging adult couples' communication after sexual activity. Guided by the post sex disclosures model, the findings indicated that post sex oxytocin levels, but not increases in pre to post sex oxytocin, were associated with men's general assessments of the benefits and risks of disclosing after sexual activity (measured separately from the sexual episode). Additionally, women's and men's benefit assessments were positively associated, and their risk assessments were negatively associated, with positive disclosures after sex. The findings offer the first known test of couples' oxytocin levels during a naturally occurring sexual episode in the home environment and have implications for researchers interested in the links between oxytocin and human behavior.